Natural killer cell metabolism. (November 2019) - Kobayashi, Takumi; Mattarollo, Stephen R.
Highlights: Different activation stimuli cause metabolic alterations in NK cells. mTOR pathway activation is a key regulator of NK cell function. NK cell dysfunction in cancer and obesity by nutrient and metabolite imbalances. Abstract: Natural killer (NK) cells are a critical component in the innate immune response against disease. NK cell function is tightly regulated by specific cytokine and activation/inhibitory receptor signalling, leading to diverse effector responses. Like all living cells, energy metabolism is a fundamental requirement for NK cell activation and survival. There is growing evidence that distinct functional profiles of NK cells are determined by alterations to cellular metabolic pathways. In this review, we summarise current literature that has explored NK cell metabolism to provide insight into how metabolic regulation controls NK cell function. We focus on metabolism pathways induced by different NK cell stimuli, metabolic regulatory proteins, and nutrient and hormonal levels in health and disease which impact on NK cell metabolic and functional activity.